Status of the BNL muon (g-2) experiment - Prigl, Ralf; Grossmann, Alex; Jungmann, Klaus; Neumayer, Paul; Putlitz, Gisbert zu (Arxiv, 2001)
The muon g-2 experiment at Brookhaven has been taking data since 1997. Analyses of the data taken in 1997 and 1998, which include about 2% of the data taken so far, have improved the experimental accuracy in the muon anomalous magnetic moment to a(mu,expt) = 1 165 921(5) x 10**(-9) (4 ppm). The value agrees with standard theory. Analysis of the 1999 data, about 25% of the existing data set, is nearing completion and analysis of the 2000 data has started. The experiment is preparing for another major data taking run, this time storing negative instead of positive muon beams.
Gesehen am 06.03.2020